2020
DOI: 10.1021/acs.jpclett.0c02317
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanide-Induced Photoluminescence in Lead-Free Cs2AgBiBr6 Bulk Perovskite: Insights from Optical and Theoretical Investigations

Abstract: Emphasis was recently placed on the Cs2AgBiBr6 double perovskite as a possible candidate to substitute toxic lead in metal halide perovskites. However, its poor light-emissive features currently make it unsuitable for solid-state lighting. Lanthanides doping is an established strategy to implement luminescence in poorly emissive materials, with the additional advantage of fine-tuning the emission wavelength. We discuss here the impact of Eu-and Yb-doping on the optical properties of Cs2AgBiBr6 thin films, obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 42 publications
1
51
0
Order By: Relevance
“…7 F 2 emission, but underwent at rap-like recombination. [33] So one can expect the further work on these phenomena and the related emission mechanism deserves to be explored in rare earth ion doped Cs 2 AgInCl 6 .…”
Section: Rare Earth Ion Doped Cs 2 Aginclmentioning
confidence: 99%
See 2 more Smart Citations
“…7 F 2 emission, but underwent at rap-like recombination. [33] So one can expect the further work on these phenomena and the related emission mechanism deserves to be explored in rare earth ion doped Cs 2 AgInCl 6 .…”
Section: Rare Earth Ion Doped Cs 2 Aginclmentioning
confidence: 99%
“…The orange and violet regions indicate decomposition pathways involving only binary compounds and ternary compounds,respectively.M odified with permission from the American Chemical Society and Wiley-VCH. [8,33] Figure 9. a) Calculated charge density difference upon X-site vacancy formation in Cs 2 AgInCl 6 .b )Calculated transitione nergy levels for intrinsic donor (blue lines) and acceptor (red lines) defects.…”
Section: Defects and Vacancies In Cs 2 Aginclmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, to explore doped Cs 2 AgInCl 6 NCs with improved PLQY and tunable emission is a main challenge. Generally, lanthanide (Ln 3+ ) ions would be the most suitable dopants for their rich and unique PL emissions in the visible to near-infrared range [28,29], which could be utilized to achieve tunable luminescence and increased PLQY [30]. Moreover, the successful incorporation of rare earth ions for the lead-based halide perovskites [31,32] and the structural similarity between lead-based and lead-free perovskites (both with the six octahedral coordination number) have provided the reference and opportunities to conduct the further lanthanide doping study on Cs 2 AgInCl 6 NCs [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…A recent experimental–computational work by Schmitz et al on Eu‐ and Yb‐doped Cs 2 AgBiBr 6 bulk perovskite, whose structure is very similar to that of Cs 2 AgInCl 6 , showed that Yb III in Cs 2 AgBiBr 6 exhibited the characteristic intense emission in the NIR region. In contrast, Eu III in Cs 2 AgBiBr 6 did not exhibit characteristic 5 D 0 → 7 F 2 emission, but underwent a trap‐like recombination [33] . So one can expect the further work on these phenomena and the related emission mechanism deserves to be explored in rare earth ion doped Cs 2 AgInCl 6 .…”
Section: Multiple Dopants In Cs2agincl6 and Their Photoluminescencementioning
confidence: 97%